Self-examination, compassion and narrative imagination in students' critical examination in science education. (June 2021) - Wiblom, Jonna; Andrée, Maria; Rundgren, Carl-Johan
Abstract: The interest of this study is in how science education may contribute to cultivating democratic citizenship in a globalised world. The drive for joint global action and a mutual sense of responsibility for achieving a sustainable future need to be balanced with consideration for inequalities, accountability and differences in agency among people around the world. This raises questions of what citizens need to know, do, and feel to respond to the contemporary and future needs of a broader humanity. We explore how Martha Nussbaum's notion of world citizenship (1997) may be used to expand the understanding of critical examination of socioscientific controversies in science education. We analyse how groups of upper secondary science students engage in a critical examination of dairy and oat milk production and consumption from multiple perspectives. The study exemplifies how the critical examination of science may be recognised not only as source critique, but also as a way to: critically examine norms, traditions and personal habits; recognise oneself as bound to others by mutual concern for human and environmental wellbeing; imagine pathways to a sustainable future; and make moral judgements on a cow's right to life.